kARAKTERISTIK PEDAGANG KAKI LIMA (PKL) DI KOTA PAYAKUMBUH - Ririn Aurelia N; Fitriana Syahar (JURUSAN GEOGRAFI FIS UNP, 2021)
This study aims to: (1) Know how the street vendors in Payakumbuh City, (2) Knowing how the distribution of the area of origin of street vendors buyers in Payakumbuh City. This type of research is descriptive with a quantitative approach using primary data and secondary data obtained through observation, interviews, questionnaires and documentation. Respondents of this research are 75 street vendors who are on Jalan Soekarno-Hatta to Jalan Jendral Sudirman Payakumbuh market. The data analysis technique used is the data analysis technique using the Rank Size Rules and Breaking Point methods. This study found: (1) The characteristics of the street vendors consist of street vendors and street vendors. (2) The distribution of areas of origin for buyers within the City of Payakumbuh is in the Parit Rantang, Ibuh, and Padang Tinggi Piliang villages. Buyers outside Payakumbuh come from Pekanbaru, Bukittinggi, and Batusangkar.